Renewable H-2 from glycerol steam reforming: effect of La2O3 and CeO2 addition to Pt/Al2O3 catalysts. - Montini, Tiziano; Singh, Rakesh; Das, Piyali; Lorenzut, Barbara; Bertero, Nicolas; Riello, Pietro; Benedetti, Alvise; Giambastiani, Giuliano; Bianchini, Claudio; Zinoviev, Sergey; Miertus, Stanislav; Fornasiero, Paolo (Chemsuschem, 2010)
Glycerol is the main byproduct of biodiesel production and its increased production volume derives from the increasing demand for biofuels. The conversion of glycerol to hydrogen-rich mixtures presents an attractive route towards sustainable biodiesel production. Here we explored the use of Pt/Al2O3-based catalysts for the catalytic steam reforming of glycerol, evidencing the influence of La2O3 and CeO2 doping on the catalyst activity and selectivity. The addition of the latter metal oxides to a Pt/Al2O3 catalyst is found to significantly improve the glycerol steam reforming, with high H-2 and CO2 selectivities. A good catalytic stability is achieved for the Pt/La2O3/Al2O3 system working at 350 degrees C, while the Pt/CeO2/Al2O3 catalyst sharply deactivates after 20 h under similar conditions. Studies carried out on fresh and exhausted catalysts reveal that both systems maintain high surface areas and high Pt dispersions. Therefore, the observed catalyst deactivation can be attributed to coke deposition on the active sites throughout the catalytic process and only marginally to Pt nanoparticle sintering. This work suggests that an appropriate support composition is mandatory for preparing high-performance Pt-based catalysts for the sustainable conversion of glycerol into syngas.
Keywords: biofuels; Glycerol; heterogeneous catalysis; platinum; supported catalysts

Challenges and opportunities in biofuels production - Srinivas, Darbha; Satyarthi, Jitendra Kumar (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
Biofuels are attractive alternative to petroleum diesel. They are renewable, non-toxic, biodegradable, carbon neutral and lead to reduced tailpipe emissions. This article presents the current state-of-art processes of their production and discusses the opportunities and future challenges in this area of research.
Keywords: Biodiesel; biofuels; Deoxygenation; Hydrotreatment; Renewable fuels; Solid catalysts; Transesterification (fatty acid glycerides); Vegetable oils/fats

Glycerol etherification using n-butanol to produce oxygenated additives for biodiesel fuel over H-beta zeolite catalysts - Nandiwale, Kakasaheb Y.; Patil, Shivraj E.; Bokade, Vijay V. (Energy Technology, 2014)
The catalytic etherification of glycerol has been systematically studied in batch process by using n-butanol to produce oxygenated additives for biodiesel fuels over various solid-acid catalysts, such as H-beta zeolite, ZSM-5, K10, etc.. The present work includes a detailed study of the optimization of the etherification process parameters, such as catalyst loading (7-20 wt% of glycerol), molar ratio of glycerol/n-butanol (1: 6 to 1: 15), speed of agitation (100-400 rpm), reaction temperature (413-453 K), and reaction time (0.5-4 h) in view of maximizing the glycerol conversion and selectivity towards mono-butyl-glycerol ether (ME). The catalyst reusability was studied using the optimized process parameters. Amongst the studied catalysts, the H-beta zeolite was found to be the most promising for the etherification of glycerol with glycerol conversion of 55% and a 98% selectivity towards ME formation. The H-beta zeolite was found to be an active and stable catalyst for up to 4 cycles. The use of n-butanol as alkylating agent is presented for first time, to the authors knowledge. The reaction was performed at milder operating conditions (0.5 MPa) than previously reported (2 MPa). A kinetic model was developed for the etherification reaction and the data obtained at optimized process parameters was used to calculate the kinetic parameters. The reaction rate constants at different reaction temperatures, activation energies, and pre-exponential factors were obtained for the etherification reaction with an accuracy of R-2 > 0.989.
Keywords: biofuels; catalysis; etherification; fuel additives; zeolites

Environmentally benign catalytic process for esterification of renewable levulinic acid to various alkyl levulinates biodiesel - Nandiwale, Kakasaheb Y.; Bokade, Vijay V. (Environmental Progress & Sustainable Energy, 2015)
This study explores, the use of modified zeolite (Micro/Meso-HZ-5) obtained by desilication post-treatment as heterogeneous catalyst for esterification of biomass derived renewable levulinic acid (LA) with different alkyl alcohols such as methanol, ethanol, n-butanol, and n-octanol aiming to produce corresponding alkyl levulinate. This method of production of alkyl levulinates would be sustainable process, as it can be used as novel miscible diesel biofuels preventing global warming by decreasing atmospheric CO2. The LA conversion obtained over Micro/Meso-HZ-5 was higher than H-ZSM-5, which is due to the combined effect of increase in Bronsted acid sites, total acidity, and other properties such as BET surface area and the generation of mesoporosity. The maximum LA conversion of 91, 95, 96, and 98% with 100% selectivity toward alkyl levulinate was obtained, when LA was being esterified over Micro/Meso-HZ-5 with methanol, ethanol, n-butanol, and n-octanol, respectively, at optimal process parameters. Micro/Meso-HZ-5 catalyst was found to be reusable for six cycles. Furthermore, pseudo homogeneous (P-H) kinetic model of the esterification of LA with the studied four alcohols were established with R-2>0.99, using the experimental data. A P-H kinetic model implies that, the esterification reaction follows second order reversible kinetics. (c) 2014 American Institute of Chemical Engineers Environ Prog, 34: 795-801, 2015
Keywords: biofuels; Esterification; kinetic model; levulinic acid; meso-HZ-5; micro

Studies of synergy between metal-support interfaces and selective hydrogenation of HMF to DMF in water - Goyal, Reena; Sarkar, Bipul; Bag, Arijit; Siddiqui, Nazia; Dumbre, Deepa K.; Lucas, Nishita; Bhargava, Suresh Kumar; Bordoloi, Ankur (Journal of Catalysis, 2016)
Metal-support interfaces play a very important role in heterogeneous catalysis. The interfacial interactions not only are responsible for stabilizing the necessary oxidation state to facilitate the reaction but also enhance the stability of the catalyst system. Nano dispersion of Ni on mesoporous nitrogen-rich carbon material has been achieved using two different synthesis methods. It was observed that nickel (0) gets stabilized by strong interfacial interaction with the nitrogen atoms of the support material, and the material was found to be very economic and efficient for the conversion of HMF to DMF in aqueous medium. The material shows >= 99% conversion to 5-(hydroxymethyl) furfural (HMF) within 6 h of reaction with 98.7% DMF selectivity. A unique correlation between synthesis methods and particle sizes with catalytic performance has been observed for these newly developed materials. Furthermore, a DFT calculation has been performed to predict the reaction mechanism. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: biofuels; Biomass; Hydrogenation; mesoporous carbon; Ni-CNx

Promotional effect of WOx in Pt-WOx/AlPO4-5 catalyzed deoxygenation of fatty acids - Janampelli, Sagar; Darbha, Srinivas (ChemistrySelect, 2017)
WOx promoted Pt/AlPO4-5 catalysts with varying Pt and W contents were prepared by wet-impregnation method and characterized. Catalysts with Pt to W weight ratio of 1: 2 exhibited higher catalytic performance than the other compositions in deoxygenation of oleic acid (OA). WOx enhanced significantly the catalytic activity of Pt and enabled quantitative conversion of OA to linear alkanes (predominantly C-18/C-17) at a temperature as low as 280 degrees C. It changed the reaction pathway from decarbonylation/ decarboxylation (DCO for Pt/AlPO4-5) to hydrodeoxygenation (HDO for Pt-WOx/AlPO4-5). It affected the particle size and redox behaviour of Pt. The enhanced H-spill over (by 14.8%) and presence of strong acid sites (300 - 500 degrees C) are the cause for the high activity of Pt-WOx/AlPO4-5 catalysts even at lower temperatures. Partially reduced WOx activates OA and leads to the HDO product (C-18). In the absence of WOx, Lewis acid sites of the support activate OA through the C=O group and Pt facilitates C-C cleavage and formation of DCO product (C-17).
Keywords: biofuels; Deoxygenation; Fatty acids; Green Diesel; Hydrocarbons

Selective and reusable Pt-WO x /Al 2 O 3 catalyst for deoxygenation of fatty acids and their esters to diesel-range hydrocarbons - Janampelli, Sagar; Srinivas, Darbha (Catalysis Today, 2017)
Tungsten oxide promoted platinum catalysts (Pt-WOx/Al2O3) of varying composition were prepared by wet impregnation method and reduced in hydrogen atmosphere. X-ray powder diffraction and photoelectron spectroscopy revealed that Pt is completely reduced to metallic state while tungsten is in +6 and +5 oxidation state. Pt crystallite and particle sizes increased (from 1.2 to 1.4 nm and 2.5 to 3 nm, respectively) in presence of WOx (CO-chemisorption and transmission electron microscopy). Tungsten addition augmented strong acid sites. It enhanced significantly the catalytic activity of Pt/Al2O3 in deoxygenation of fatty acids and their methyl esters. Tungsten altered the reaction pathway from decarbonylation/decarboxylation to hydrodeoxygenation. A catalyst with 4 wt% Pt and 8 wt% W exhibited high catalytic performance. Complete conversion of oleic acid and octadecane product selectivity in the range 67.1 − 80.8% was obtained. Pt-WOx/Al2O3 is a stable and reusable fatty acid deoxygenation catalyst.
Keywords: biofuels; Deoxygenation; Diesel-range hydrocarbons; Fatty acids; Pt catalyst

Hydrodeoxygenation of vegetable oils and fatty acids over different group VIII metal catalysts for producing biofuels - Janampelli, Sagar; Darbha, Srinivas (Catalysis Surveys From Asia, 2019)
Energy security and environment protection are two important aspects of sustainable development. Biofuels are renewable and carbon neutral. They are suitable replacement for conventional fossil derived transport fuels. Their use leads to sustainable development. Among several technological options, catalytic hydrodeoxygenation of vegetable oils leading to diesel-range hydrocarbons is the most attractive approach for producing biofuels. The green diesel, thus produced, could be blended with petro-diesel or used as standalone fuel in the conventional diesel engines. Our research group has been active in developing efficient solid catalysts for hydroprocessing of vegetable oils. This account presents some of our efforts using supported group VIII metals and the importance of electronic contact between metal and support on the catalytic activity and hydrodeoxygenation selectivity in hydroprocessing of vegetable oils.
Keywords: biofuels; Catalysis over group VIII metals; Deoxygenation; Hydroprocessing; Renewable diesel

Perception of glycerol carbonate as green chemical: synthesis and applications - Gade, Swapna M.; Saptal, Vitthal B.; Bhanage, Bhalchandra M. (Catalysis Communications, 2022)
Glycerol carbonate (GC) is a prominent component in industrial practice and has a remarkable potential for the sophisticated applications. While GC has come into prominence due to the perceived overflow of glycerol (GLY) as a coproduct of biodiesel industry, its contemporary and future downstream applications are driving tremendous interest in recent years. This review comprises strategies for glycerol carbonate synthesis, properties and its applications. The conversion of GLY to GC via transesterification has appeared in consensus to be the most promising route. A detailed explanation of the effect of the catalysts and operating conditions on the GC yield to provide an updated understanding of the process are summarized. Future directions for GC production through catalytic transesterification are also discussed.
Keywords: Biodiesel; biofuels; catalysis; Glycerol; Glycerol carbonate; green chemistry; transesterification

Synergistic effect of acidic-basic features of copper-doped layered double hydroxides nanocatalysts in valorization of biomass-derived furfural to biofuels - Gode, Nilesh G.; Nagpure, Atul S.; Rewatkar, Suresh B.; Bhagat, Shailesh K.; Deshmukh, Ganpat D.; Saini, Ajay (ChemPlusChem, 2025)
Valorization of biomass-derived chemicals into high-quality compounds and biofuels is enormously fundamental to diminish dependence on fossil-based resources. Furfural is a bio-based valuable compound which can be proficiently upgraded to 4-(2-furyl)-3-buten-2-one (FAc) and 1,4-pentadiene-3-one, 1,5-di-2-furanyl (F 2 Ac) via aldol condensation of furfural with acetone. In the present work, efficient Cu-doped Mg-Al layered double hydroxides (LDH) nanocatalysts are fabricated by coprecipitation and are exploited for furfural conversion to obtained FAc and F 2 Ac. The structure-activity relationship is scrutinized by characterizing fresh and spent nanocatalysts via numerous techniques. The good correlation between the amount of weak acidic-weak basic catalytic sites and nanocatalysts performance is established. The superior performance of Cu-0.1 nanocatalyst (Cu-content = 1.85 wt%) in aldol condensation is attributed to the presence of optimum weak acidic sites (0.21 mmol g-1) and weak basic sites (0.36 mmol g-1), synergistic acidic-basic effect, nano-sized Cu(OH) 2 nanoparticles (1.6 nm), high BET surface area (181 m2 g-1), and mesoporous architecture of material. Cu-0.1 nanocatalyst delivered 98% FAc selectivity with 100% furfural conversion at 85 degrees C. Furthermore, at 100 degrees C, the nanocatalyst gives 55% F 2 Ac selectivity with 73% furfural conversion. The catalyst displays good recyclability (7 recycles) and stability. Plausible mechanistic pathway for transformation of furfural to FAc and F 2 Ac is proposed.
Keywords: Aldol condensation; biofuels; biomass valorization; nanocatalysis; synergistic effect